Comparative evaluation of shear bond strength of two different chairside soft liners to heat processed acrylic denture base resin: An in vitro study - N Rajaganesh; S Sabarinathan; N S Azhagarasan; Chitra Shankar; Jaya Krishnakumar; S Swathi (Wolters Kluwer Medknow Publications, 2016)
Background: Chairside softliners are used more frequently than is reported and studies regarding the bond strength of chairside softliners to heat-polymerized denture base resin are few and limited. Hence, this study was conducted to comparatively evaluate the shear bond strength of two chairside soft relining materials viz., autopolymerizing plasticized acrylic resin liner and a silicone-based liner bonded to heat polymerized polymethyl methacrylate denture base resin and to analyze the mode of interfacial bond failure. Materials and Methods: Forty test specimens (n = 40) were prepared by bonding plasticized acrylic- and silicone-based soft liner to heat polymerized acrylic resin blocks. Twenty specimens, ten from each group, were subjected to thermal cycling and later to shear bond strength testing. The debonded specimens were then qualitatively analyzed for the mode of failure using scanning electron microscopy. The results obtained were tabulated and statistically analyzed. Results: The mean shear bond strength values obtained for acrylic-based soft liner before and after thermal cycling were 0.3365 ± 0.025 MPa and 0.3164 ± 0.04 MPa, respectively. The mean shear bond strength values obtained for silicone-based soft liner before and after thermal cycling were 0.4159 ± 0.025 MPa and 0.4335 ± 0.02 MPa, respectively. Silicone-based soft liner showed higher shear bond strength than the acrylic-based both before and after thermal cycling (P = 0.0001). Scanning electron microscopy analysis showed a predominantly mixed mode of failure with silicone-based liner and predominantly adhesive mode of failure with acrylic-based soft liner. Conclusion: The silicone-based soft liner showed higher shear bond strength to heat polymerized acrylic resin than acrylic-based soft liner both before and after thermal cycling.